STUDI KOMPARATIF PENAFSIRAN FAKHRUDDIN AL-RAZI DAN IBN ‘ARABI TENTANG MAKNA MARAJ AL-BAHRAYN DALAM AL-QUR’AN - Nadia Zahro; Hajam Hajam; Lukman Zain MS (UIN Siber Syekh Nurjati Cirebon, 2021)
This paper examines the meaning of the word Maraja al-Baḥrayn according to the interpretation of Fakhruddin al-Razi and Ibn 'Arabi. These two commentators were chosen to find out more about the meaning of the word from a Sufistic and scientific point of view, because at first glance, the two perspectives seem to contradict each other. In addition, this study also aims to find out how the interpretation of Maraj al-Bahrayn word according to Al-Razi and Ibn 'Arabi and compare their interpretation of that word. The interpretations of the two figures were analyzed using the discussion hermeneutic method from Schleiermacher.Tulisan ini menggkaji tentang makna kata Maraja al-Baḥrayn menurut panafsiran Fakhruddin al-Razi dan Ibn ‘Arabi. Kedua mufassir ini dipilih untuk mengetahui lebih dalam lagi makna kata tersebut dari sudut pandang sufistik dan sains, karena jika dilihat sekilas, kedua perspektif tersebut seolah saling bertolak belakang satu sama lain. Selain itu, kajian ini juga bertujuan untuk mengetahui bagaimana penafsiran kata Maraj al-Bahrayn menurut Al-Razi dan Ibn ‘Arabi serta membandingkan penafsiran keduanya terhadap kata tersebut. Penafsiran kedua tokoh tersebut dianalisa dengan meggunakan metode hermeneutika pembahasan dari Schleiermacher.